Clinical characteristics of patients under 40 years old with early-onset hyperuricaemia: a retrospective monocentric study in China. Issue 8 (27th August 2019) - Zhang, Yi; Yang, Yong; Xue, Leixi; Wen, Jian; Bo, Lin; Tang, Mei; Yang, Ru; Yan, Dong; Liu, Zhichun
Abstract : Objective: To investigate the clinical characteristics of patients with early-onset hyperuricaemia (HUC). Methods: A retrospective study using data from the Second Affiliated Hospital of Soochow University was conducted. 623 patients with HUC were divided into early-onset group and late-onset group. Another 201 healthy subjects ≤40 years old were regarded as control group. The data of physical measurements and biochemistry test were collected. Clinical data of early-onset group were compared with late-onset group and control group by analysis of variance (ANOVA) and χ 2 test. Principal component analysis (PCA) was applied. Logistic regression was used to identify the clinical factors correlated with patients with early-onset HUC. Results: The patients of early-onset group had different body mass index (BMI), serum albumin, alanine transaminase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (AKP), gamma-glutamyltransferase (GGT), creatinine (Cr), triglyceride (TG), total cholesterol (TC), low density lipoprotein (LDL), TG/high density lipoprotein (HDL) ratio, HDL and percentage of males, hypertension (HBP) as well as fatty liver compared with healthy people in the control group. Early-onset group patients had different albumin, ALT, fasting blood glucose, Cr, percentage of males and HBP compared with late-onset group patients. PCA identified four significant patterns including PC1 (labelled 'TG and HDL'), PC2 (labelled 'fatty liver and liver enzymes'), PC3 (labelled 'TC and LDL') and PC4 (labelled 'AKP'). The results of univariate and multivariate logistic regression analysis showed that BMI, HBP and albumin were correlative factors for early onset of HUC when the patients with early-onset and late-onset HUC were involved, while gender, BMI, PC1, PC2 and PC4 were correlative factors for early-onset HUC when the early-onset and control groups were involved. Conclusion: This study described a group of patients with early-onset HUC with distinct clinical features. Gender, BMI, 'TG and HDL', 'fatty liver and liver enzymes' and 'AKP' have higher values than HBP, type 2 diabetes mellitus and 'TC and LDL' in patients under 40 years old with early-onset HUC.